2022
DOI: 10.1186/s13054-022-04108-8
|View full text |Cite|
|
Sign up to set email alerts
|

Co-infection and ICU-acquired infection in COVID-19 ICU patients: a secondary analysis of the UNITE-COVID data set

Abstract: Background The COVID-19 pandemic presented major challenges for critical care facilities worldwide. Infections which develop alongside or subsequent to viral pneumonitis are a challenge under sporadic and pandemic conditions; however, data have suggested that patterns of these differ between COVID-19 and other viral pneumonitides. This secondary analysis aimed to explore patterns of co-infection and intensive care unit-acquired infections (ICU-AI) and the relationship to use of corticosteroids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 46 publications
2
8
1
Order By: Relevance
“…While distinguishing pure viral sepsis from bacterial sepsis related to a non–SARS-CoV-2 coinfection or superinfection is challenging with an EHR-based approach, only a minority of patients with SARS-CoV-2–associated sepsis had positive blood or sputum cultures identified, supporting SARS-CoV-2 itself as the primary driver of sepsis in most cases. Numerous prior studies have demonstrated that bacterial coinfections are the exception rather than the norm for patients hospitalized with COVID-19 . However, these patients are at high risk for nosocomial bacterial infections, consistent with our observation that many more patients with SARS-CoV-2–associated sepsis had positive cultures across their entire hospitalizations …”
Section: Discussionsupporting
confidence: 90%
“…While distinguishing pure viral sepsis from bacterial sepsis related to a non–SARS-CoV-2 coinfection or superinfection is challenging with an EHR-based approach, only a minority of patients with SARS-CoV-2–associated sepsis had positive blood or sputum cultures identified, supporting SARS-CoV-2 itself as the primary driver of sepsis in most cases. Numerous prior studies have demonstrated that bacterial coinfections are the exception rather than the norm for patients hospitalized with COVID-19 . However, these patients are at high risk for nosocomial bacterial infections, consistent with our observation that many more patients with SARS-CoV-2–associated sepsis had positive cultures across their entire hospitalizations …”
Section: Discussionsupporting
confidence: 90%
“…Here, we reported 16.3% (95%CI 13.0–21.9%) of COVID-19 patients with bacterial co-infection, which was slightly higher than the previously reported bacterial co-infection rate among mixed COVID population with a high degree of heterogeneity [ 7 , 8 , 16 , 17 ]. In a meta-analysis, bacterial co-infection and secondary infections were identified in 3.5% and 14.3% of patients respectively [ 18 ].…”
Section: Discussioncontrasting
confidence: 78%
“…To date, there is no prospective interventional study that evaluated the impact of corticosteroid use on the incidence of VAP, as the RECOVERY study itself did not include it as an outcome. However, there is a growing body of evidence in the literature pointing out the increased risk of developing VAP in COVID-19 patients treated with corticosteroids [ 16 19 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%